Charlie Chaplin : the beauty of silence - Schroeder, Alan. (New York : Franklin Watts, 1997)
Discusses the life, career, and creative contributions of the actor and comedian.
Includes bibliographical references (p. 149-150) and index.
Booklist.
School Library Journal.
Booklist, June 1997.
School Library Journal, June 1997.
Young Adult
Keywords: Chaplin, Charlie, -- 1889-1977 -- Juvenile literature; Chaplin, Charlie, -- 1889-1977.; Chaplin, Charlie, -- 1889-1977.; Comedians -- United States -- Biography -- Juvenile literature; Motion picture actors and actresses -- United States -- Biography -- Juvenile literature; Actors and actresses; Comedians; Actors -- United States -- Biography; Comedians -- United States -- Biography